Re-meaning the other: interculturality shaping in the development and intervention of social work (2020)
To take part from the intercultural mode from social work implies going deep into the meaning that is traditionally assigned to the "other", in a dispute regarding the shaping of subjectivities, these recognize the difference and make visible its grammatical and methodological influence in the reshaping and uncertainty what implies the social aspect. From this perspective, the present article of reflection is a product of research and teaching processes: It seeks to reshape the trajectory in the understanding of the "other" from the formation and intervention of Social Work, starting from the transition from the functional to the critical interculturality, reconstructing the stay of the social aspect under the critical perspective, to weave relationships from otherness other insurgents between subjectivities. The stated purpose was reached from the analysis of different discourses on the subject, in order to explore and reveal the uses and abuses of power that are generated in social interactions and discourses, which are impregnated by connotations of exclusion, discrimination and domination , which are most of the time accepted and legitimized from the political level, therefore, its visibility enables emancipations and transformations in social dynamics. To conclude, it is established that in Social Work historically, conceptual denominations have been assumed that prefigure an image of the other and of professional relationships, so that the discursive plots are one of the inventive resources of the other, in which anthropological understandings linked to the political-cultural statutes of the west are included, leading to overcoming functional interculturality, towards an ethical-political commitment to critical interculturality.